OPERATIONAL EVALUATION OF CROSSING VESSELS ON THE TANJUNG KALI-TANJUNG API API CROSSING - Firzatullah, Raden Muhamad; Ilham, Chairul Insani; Yuda, Dimas Pratama; Puspitasari, Novrianti; Abdul Azis, M. Dadang; Tiofana, Mega Elfi (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2024)
Tanjung Kalian Crossing Port is a port located in West Bangka Regency, Bangka Belitung Islands Province. The crossing transportation service at the Tanjung Kalian Crossing Port is one of the prima donnas for service users because this port is the gateway in and out to South Sumatra Province where it has 14 ships with 9 ships operating every day. The load factor at the Tanjung Kalian Crossing Port has currently reached the maximum limit. However, the operation of ships on this track is not in accordance with the minimum service standards for ship operation and the ideal departure frequency. In order to improve the quality of service and the safety of service users, it is necessary to balance the needs of service users and transportation service providers. The methods used in this study are load factor analysis, analysis of conformity with minimum service standards for ship operation, analysis of ship needs, and scheduling analysis. Based on the results of the analysis of the load factor calculation, it shows that the load factor exceeds the ideal capacity of the ship. The minimum service standards for ship operations have also not been met because the ship's departure time and the average speed of the regular ship are not in accordance with the existing rules. There is a difference in Existing conditions with the results of the analysis of ship needs and optimal ship scheduling so that it is necessary to reschedule according to the needs of service users.